Neonatal Mortality Trend at the University Clinic of Gynecology and Obstetrics- SKOPJE in the period of 2011-2017 - Gabriela Bushinoska Ivanova; Jasna Bushinoska (International Organization of Scientific Research (IOSR), 2020)
Abstract: INTRODUCTION: Neonatal mortality is the percent of neonatal (infant) mortality of the live- born neonates per thousand live births, in the neonatal period from 0-28 days after delivery, or those born after 22 gestation weeks of pregnancy with birth weight more than 500 g. The neonatal mortality can be divided into early neonatal mortality, which covers the period of 0-7 days after delivery (168h), regardless of the stage of pregnancy, and late neonatal mortality that includes the mortality of live-born infants in 8 until before 28 days after delivery. RESEARCH PURPOSE: The purpose of this paper is to show the percentage of neonatal mortality among live- born neonates at the UCGO-Skopje from 0-28 days after delivery, and the trends of movement of the mortality in the period 2011-2017 year. MATERIAL AND METHODS: This retrospective analysis elaborates on neonatal mortality or mortality in live- born neonates in the period 0-28 days after delivery at the UCGO-Skopje, in the period of 7 years (from 2011 to 2017), in relation to the total number of births in that period. The data is collected from the Info Centre and the histories of the disease of women that gave birth and the newborns at UCGO-Skopje during this period. RESULTS: During this period of 7 years at UCGO-Skopje, there were 36,733 live- born newborns, out of which 912 newborns died in the neonatal period after delivery, from 0-28 days after delivery. The results show that the number of early neonatal deceased newborns, 0-7 days after birth, is higher and is especially significant in the first 24 hours after delivery. The number of late neonatal deaths from 8 until before 28 days after delivery is also high. The total neonatal mortality of UCGO- Skopje in this 7 year period is 24.82 ‰, or 24.8 neonatal deaths in the neonatal period after delivery (0-28 days) per thousand live births. The highest neonatal mortality rate of 33.81‰ was recorded in 2017, while the lowest rate was 17.19 ‰ , recorded in 2015. CONCLUSION: The neonatal mortality rate in Macedonia is quite high, higher than in the countries in our surroundings, the Balkan countries and the mid- developed countries of the world.
Keywords: neonatal mortality; early neonatal mortality; late neonatal mortality; Macedonia